2010
DOI: 10.1073/pnas.1012977107
|View full text |Cite
|
Sign up to set email alerts
|

IκBζ is essential for natural killer cell activation in response to IL-12 and IL-18

Abstract: IκBζ, encoded by Nfibiz , is a nuclear IκB-like protein harboring ankyrin repeats. IκBζ has been shown to regulate IL-6 production in macrophages and Th17 development in T cells. However, the role of IκBζ in natural killer (NK) cells has not be understood. In the present study, we found that the expression of IκBζ was rapidly induced in response to IL-18 in NK cells, but not in T cells. Analysis of Nfkbiz −/− mice revealed that IκBζ was essential for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 35 publications
2
46
0
Order By: Relevance
“…However, after our manuscript received its initial review, a similar finding in murine NK cells was submitted and published. 39 As described here in humans, this work demonstrates the role of IB in IFN-␥ production in murine NK cells in response to IL-12 and IL-18. Importantly, the murine work documents the significant role that IB plays in host defense against murine cytomegalovirus infections.…”
Section: Discussionmentioning
confidence: 62%
“…However, after our manuscript received its initial review, a similar finding in murine NK cells was submitted and published. 39 As described here in humans, this work demonstrates the role of IB in IFN-␥ production in murine NK cells in response to IL-12 and IL-18. Importantly, the murine work documents the significant role that IB plays in host defense against murine cytomegalovirus infections.…”
Section: Discussionmentioning
confidence: 62%
“…Engagement of TLR2 may enhance IFNγ secretion through the activation of NF-kB and Ik-Bzeta, similarly to IL-18R activation (Akira et al, 2006). The late increase of HCMV-dependent IFNγ mRNA levels is reminiscent of the kinetics of IFNγ production upon IL-12+IL-18 stimulation in NK cells (Miyake et al, 2010; Kannan et al, 2011). Of note, two genetic studies have shown that specific TLR2 polymorphisms condition the probability to develop CMV disease in transplant recipients (Kijpittayarit et al, 2007; Kang et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…This gene has been shown to have several functions, including roles in natural killer cell activation 31 and monocyte recruitment 32. Recently, however, NFKBIZ has also been shown to be a critical regulator of Th17 development through its interaction with ROR nuclear receptors 33.…”
Section: Box: Selected Candidate Genes In the Newly-associated Ibd Sumentioning
confidence: 99%